Association of obstructive sleep apnea with risk of serious cardiovascular events: a systematic review and meta-analysis - Loke, Yoon K; Brown, J William L; Kwok, Chun Shing; Niruban, Alagaratnam; Myint, Phyo K (Circulation Cardiovascular quality and outcomes, 2012)
The relationship between obstructive sleep apnea (OSA) and cardiovascular events remains unclear. We conducted a systematic review to determine the incident risk of cardiovascular events among patients with OSA. We searched MEDLINE and EMBASE in January 2011 for prospective studies that followed up patients with OSA for incident ischemic heart disease, stroke, and cardiovascular mortality. Outcomes data were pooled using random effects meta-analysis and heterogeneity assessed with the I(2) statistic. Regression analysis was performed to evaluate the effects of different gradations of OSA severity based on apnea-hypopnea index. We identified 9 relevant studies from 1731 citations. OSA was associated with incident stroke in a meta-analysis of 5 studies (8435 participants), odds ratio (OR) 2.24; 95% confidence interval (CI), 1.57-3.19; I(2)=7%. A significant association was seen in studies that were predominantly on men; OR, 2.87; 95% CI, 1.91-4.31, whereas data on women were sparse. In the overall analysis of 6 studies (8785 participants), OSA was nonsignificantly associated with ischemic heart disease (OR, 1.56; 95% CI, 0.83-2.91), with significant findings in the 5 studies that recruited mainly men (OR, 1.92; 95% CI, 1.06-3.48). Substantial heterogeneity was noted (I(2)=74%). OSA was linked to cardiovascular death in 2 studies involving 2446 participants (OR, 2.09; 95% CI, 1.20-3.65, I(2)=0%). Regression analysis showed greater likelihood of stroke or cardiovascular events with increasing apnea-hypopnea index values. OSA appears to be associated with stroke, but the relationship with ischemic heart disease and cardiovascular mortality needs further research.